Hubungan Kecacingan dan Status Gizi Balita Usia 2-5 Tahun di Beberapa Posyandu di Wilayah Kebon Jeruk, Kota Jakarta Barat - Sari, Monica Puspa; Susilowati, Rina Priastini; Tekege, Maryana Yenieke; Makatita, Cindy Pricillia Vika Vebriza (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Introduction: Soil-transmitted helminth (STH) infections are a global health problem, especially among young children in developing countries. These infections affect children's nutritional status through various mechanisms, such as impaired nutrient absorption and chronic blood loss. Purpose: This study aims to analyze the relationship between STH infection and the nutritional status of children aged 2–5 years at several integrated Posts in the Kebon Jeruk subdistrict of West Jakarta. Method: This study used an analytic descriptive design with a cross-sectional design. A total of 153 toddlers were selected through a total sampling technique from six health posts. Worm infestation status was determined through stool examination using the Kato-Katz method. Nutritional status was assessed using three anthropometric indicators: weight for age, height for age and weight for height based on the World Health Organization Child Growth Standards. Data analysis was performed using the Fisher test. Results: The prevalence of worm infection in toddlers was 5,2%. Ascaris lumbricoides was the most common cause, with mild infection rates. Based on nutritional status, most toddlers infected with STH had normal weight for age, normal height for age, and good nutritional weight for height. There was no significant relationship between STH infections and nutritional status (p>0.05). Conclusion: The prevalence of STH infections in toddlers in the study was quite low. There was no significant association between STH infections and nutritional status in toddlers. Continuous prevention and control interventions for worm infection, along with routine monitoring of nutritional status, are needed to ensure worm-free status.